Investigating the Electrical and Optical Properties of Nickle and Strontium Co-Doped CsPbBr 3 Nanocrystals: Potential Absorber Material for Perovskite Solar Cells - Saqib Ali; Sofia Javed; Muhammad Aftab Akram; Nadia Shahzad(US-Pakistan Center for Advance Studies in Energy; Muhammad Adnan; Muhammad Usman; Maryam Basit; Faiza Rizwan; Muhammad Mujahid (Transactions on electrical and electronic materials, 2024)
In this study, the optoelectronic characteristics of cesium-based all-inorganic perovskite (AIP) nanocrystals (NCs) are examined in relation to Sr/Ni doping. These nanocrystals are synthesized via the hot injection method and then examined for compositional, morphological, optical, and electrical characteristics. Scanning electron microscopy reveals the homogeneous and compact NCs clusters while Atomic Force Microscopy (AFM) studies shows smooth film morphology with a narrow size distribution. X-ray diffraction analysis confirmed the monoclinic perovskite structure and excellent crystallinity. Similarly, Fourier-transform infrared spectroscopy has shown evidence for the existence of long-chain organic ligands employed for the stability and passivation of the NCs. High absorbance in the visible region is seen by UV–Visible spectroscopy, with a band gap of 2.44-2.48 eV while steady-state photoluminescence spectroscopy indicates low lattice defects and high crystallinity. Doping with Sr/Ni increased the bulk charge carrier concentration up to 3.70 × 10 16 cm -3 and decreased the resistivity to 4.61 × 10 3 Ω cm as compared to 1.45 × 10 13 cm -3 and 8.58 × 10 3 Ω cm respectively according to measurements made using the hall effect measurments. The doped AIP NCs displayed excellent thermal stability up to 545 °C. The Ni/Sr doping has resulted in obtaining improved properties in CsPbBr 3 perovskite NCs for optoelectronic application. KCI Citation Count: 0